Exercise training and pulmonary arterial hypertension: A review of the cardiac benefits - Soares, L. L.; Drummond, F. R.; Lavorato, V. N.; Carneiro-Junior, M. A.; Natali, A. J. (Science & Sports, 2018)
Aims: Patients of pulmonary arterial hypertension (PAH) exhibit reduced functional capacity and exercise tolerance. Despite the evidences that exercise training is beneficial to this population, it is still being tested whether regular physical exercise can mitigate the complications of PAH. The aim of this review was to point out the cardiac functional and structural adaptations to exercise training in animal models of PAH, and highlight the cellular and molecular mechanisms underlying the benefits of exercise to individuals with PAH. News: A systematic review of original articles published in PubMed and ScienceDirect databases was conducted by two independent researchers. Relevant information on animal model, exercise protocol, cardiac functional and structural adaptations was extracted and discussed. The results show that in rats with monocrotaline-induced PAH (50-60mg/kg body weight), the predominant model used, aerobic continuous (treadmill running) and intermittent (voluntary wheel running) exercise training of moderate intensity, performed either prior or during the development of PAH, promote benefits to the myocardium. Moreover, the articles reveal that the cardiac function (i.e. restoration of right ventricle systolic and diastolic pressure, AT/ET ratio, TAPSE and cardiomyocyte contractility) and structure (i.e. reduced hypertrophy and fibrosis; improved profile of proteins related to cellular contraction and inflammatory response) are enhanced by exercise training. Furthermore, these exercise adaptations result in augmented exercise capacity and survival of animals with PAH. Conclusion: Regular aerobic exercise of moderate intensity promotes cellular and molecular adaptations that improve myocardial function and structure along with increased exercise tolerance and survival.